2022
DOI: 10.3390/ijms23105521
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Oxidative Stress and Inflammation-Related Genes in Nasal Mucosa and Nasal Polyps from Patients with Chronic Rhinosinusitis

Abstract: Chronic rhinosinusitis (CRS) is a prevalent, multifaceted inflammatory condition affecting the nasal cavity and the paranasal sinuses, frequently accompanied by formation of nasal polyps (CRSwNP). This apparently uniform clinical entity is preceded by heterogeneous changes in cellular and molecular patterns, suggesting the presence of multiple CRS endotypes and a diverse etiology. Alterations of the upper airway innate defense mechanisms, including antimicrobial and antioxidant capacity, have been implicated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Previous studies generally focused on the relationship between control and CRS nasal tissues with respect to selected oxidative-stress-related genes, such as iNOS, HO-1, SOD, PRDX, and others [ 14 , 15 , 39 , 52 ]. In this study, we systemically analyzed NP tissues using 84 preset oxidative-stress-related genes, targeting and providing a whole analytic picture of up- and downregulated genes that might contribute to the generation of oxidative stress, including lipid peroxidation and protein nitrotyrosination during nasal polyposis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies generally focused on the relationship between control and CRS nasal tissues with respect to selected oxidative-stress-related genes, such as iNOS, HO-1, SOD, PRDX, and others [ 14 , 15 , 39 , 52 ]. In this study, we systemically analyzed NP tissues using 84 preset oxidative-stress-related genes, targeting and providing a whole analytic picture of up- and downregulated genes that might contribute to the generation of oxidative stress, including lipid peroxidation and protein nitrotyrosination during nasal polyposis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, at the molecular level, the expression of oxidative stress-and inflammationrelated genes in nasal polyps from patients with CRSwNP was evaluated. A significantly lower difference in the expression levels of transcription of antioxidant enzymes, including superoxide dismutase (SOD) and peroxiredoxin-2 (PRDX2), was reported, independent of age, sex, and smoking in patients with CRSwNP [12]. These results correspond to reduced SOD capacity with the increase in oxidative stress.…”
Section: Chronic Rhinosinusitis (Crs) and Nasal Polyps (Np)mentioning
confidence: 91%
“…The source of PACAP in human biological fluids is mainly unknown, but these studies have highlighted the potential use of PACAP as a biomarker in certain diseases, where changes can reflect the presence and/or progression of a disease (127). Among others, PACAP has a potential biomarker value in dilatative cardiomyopathy, cardiac infarct, Parkinson's disease, migraine, polytrauma and chronic rhinosinusitis (127,(137)(138)(139)(140)(141). A most recent study has highlighted the potential use of PACAP, together with calcitonin gene related peptide (CGRP), in differentiating pediatric migraine from non-migraine headaches (142), while another recent study has shown the association between COVID-survival and VIP/PACAP plasma levels (143).…”
Section: Human Findingsmentioning
confidence: 99%